2007
DOI: 10.1007/s11104-007-9481-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nitrogen fixation and ammonium assimilation in common bean (Phaseolus vulgaris L) subjected to iron deficiency

Abstract: A greenhouse experiment was carried out aiming to study the effect of iron deficiency on nitrogen fixation and ammonium assimilation in common bean nodules. Host-plant and nodule growth, symbiotic nitrogen fixation, glutamine synthetase (GS) and glutamate dehydrogenase (GDH) were analyzed in two common bean varieties subjected to iron deficiency. Results showed that host-plant and nodules growth, nitrogen fixation and GS activity decreased when under Fe-deficiency against an important increase of ammonium accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…It has been demonstrated that the application of Fe nutrition to plants under drought condition can enhance tolerance as it leads to production of assimilates (Sultana et al, 2001;Rotaru, 2011;Pourgholam et al, 2013) (Table 1). It has also been reported that legumes have positive responses to Fe nutrition (Slatni et al, 2008;Rotaru, 2011). Furthermore, Mahmood et al (1990) demonstrated that the application of Fe increased the yield of wheat plants.…”
Section: Iron and Drought Stressmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been demonstrated that the application of Fe nutrition to plants under drought condition can enhance tolerance as it leads to production of assimilates (Sultana et al, 2001;Rotaru, 2011;Pourgholam et al, 2013) (Table 1). It has also been reported that legumes have positive responses to Fe nutrition (Slatni et al, 2008;Rotaru, 2011). Furthermore, Mahmood et al (1990) demonstrated that the application of Fe increased the yield of wheat plants.…”
Section: Iron and Drought Stressmentioning
confidence: 95%
“…Modifies drought resistance through its effects on root growth Snyder and Schmidt, 1974;Glinski et al, 1992 Iron application Turf grasses Leads to color enrichment and growth improvement in Fe-deficient conditions Deal and Engel, 1965;Minner and Butler, 1984;Glinski et al, 1992 Iron application Turf grass Gives darker green color for cool-season in Fe-sufficient condition Snyder and Schmidt, 1974;Carrow et al, 1988;Schmidt and Snyder, 1984;Yust et al, 1984;Wehner and Haley, 1990;Glinski et al, 1992 Iron application Legumes Positive responses to iron nutrition Slatni et al, 2008;Rotaru, 2011 Application of Iron with Zinc…”
Section: Iron and Heavy Metal Stressmentioning
confidence: 99%
“…In this study, the presence of rhizobial nodulation appeared to restrict the establishment of bean FRR at pod maturity stage and increase yield levels under different soil conditions on a regional basis. However, detection of high nodulation in only 12.3% of the fields may reflect the influence of iron deficiency in restricting legume-rhizobia symbiosis and plant growth (Slatni et al, 2008) that is a major problem in calcareous soils of Zanjan. Definitely, further investigation is required to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the symbiotic system of legumes is very sensitive to Fe deficiency (Slatni et al, 2008). Therefore, there was a positive effect on atmospheric N-fixation of soybean plants that reflected directly on leaf N, chlorophylls a and b and total chlorophyll (Figures 1 and 2).…”
Section: Soybean Growth and Development At 85 Days From Sowingmentioning
confidence: 96%